2020
DOI: 10.3153/ar20017
|View full text |Cite
|
Sign up to set email alerts
|

Current status of economically important diadromous fish species of Turkey; European eel, Black Sea trout and sturgeon species

Abstract: Turkey has a rich variety of fish species in its rivers with a total length of 177 714 km. Freshwater fish live in rivers, streams, creeks, dam lakes, natural lakes, wetland areas, etc. The life of migratory fish is threatened by the anthropogenic impact on aquatic habitats. Human activities that disrupt river integrity can be listed as; dam and hydro power plant constructions, high levees, sluices, weirs and bridges, sand-gravel quarries, recreational works, wetland depletion, water pollutions, overfishing, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Owing to the specific water current characteristics in the southern part of the Black Sea (Shapiro, 2009), it is difficult to specify which of these rivers is home to the orange cluster individuals. The presence of stellate sturgeon young‐of‐the‐year in the lower section of the Sakarya River was also reported by Memiş et al (2019, 2020). However, based on population structure, all of the individuals sampled in the proximity of the Sakarya River showed signs of admixture.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Owing to the specific water current characteristics in the southern part of the Black Sea (Shapiro, 2009), it is difficult to specify which of these rivers is home to the orange cluster individuals. The presence of stellate sturgeon young‐of‐the‐year in the lower section of the Sakarya River was also reported by Memiş et al (2019, 2020). However, based on population structure, all of the individuals sampled in the proximity of the Sakarya River showed signs of admixture.…”
Section: Discussionsupporting
confidence: 77%
“…No spawning event was reported based on a larvae and juveniles survey, although adult sturgeons were found in the Yes ¸ilırmak River. For the Kızılırmak River, no data are available (Zengin et al, 2010), whereas, in the Sakarya River, reproduction was confirmed by capturing one young-of-the-year stellate sturgeon in the lower section of the river (Memis ¸et al, 2019(Memis ¸et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sturgeons have high economic value, which have become an important aquaculture species due to caviar (Song et al, 2022). Wild populations of sturgeons have decreased because of legal or illegal overfishing, dams and pollution (Williot et al, 2005; Memiş et al, 2020). Acipenser gueldenstaedtii , (Danube sturgeon) is a migratory fish species belonging to the Acipenseridae family that naturally distributing in the Caspian Sea, Azov Sea and Black Sea (Song et al, 2022).…”
Section: Introductionmentioning
confidence: 99%